Salinity affects microbial activity and soil organic matter content in tidal wetlands. (13th January 2014) - Morrissey, Ember M.; Gillespie, Jaimie L.; Morina, Joseph C.; Franklin, Rima B.
Abstract Climate change‐associated sea level rise is expected to cause saltwater intrusion into many historically freshwater ecosystems. Of particular concern are tidal freshwater wetlands, which perform several important ecological functions including carbon sequestration. To predict the impact of saltwater intrusion in these environments, we must first gain a better understanding of how salinity regulates decomposition in natural systems. This study sampled eight tidal wetlands ranging from freshwater to oligohaline (0–2 ppt) in four rivers near the Chesapeake Bay (Virginia). To help isolate salinity effects, sites were selected to be highly similar in terms of plant community composition and tidal influence. Overall, salinity was found to be strongly negatively correlated with soil organic matter content (OM%) and C : N, but unrelated to the other studied environmental parameters (pH, redox, and above‐ and below‐ground plant biomass). Partial correlation analysis, controlling for these environmental covariates, supported direct effects of salinity on the activity of carbon‐degrading extracellular enzymes (β‐1, 4‐glucosidase, 1, 4‐β‐cellobiosidase, β‐D‐xylosidase, and phenol oxidase) as well as alkaline phosphatase, using a per unit OM basis. As enzyme activity is the putative rate‐limiting step in decomposition, enhanced activity due to salinity increases could dramatically affect soil OM accumulation. Salinity was also found to be positively related to bacterial abundance (qPCR of the 16S rRNA gene) and tightly linked with community composition (T‐RFLP). Furthermore, strong relationships were found between bacterial abundance and/or composition with the activity of specific enzymes (1, 4‐β‐cellobiosidase, arylsulfatase, alkaline phosphatase, and phenol oxidase) suggesting salinity's impact on decomposition could be due, at least in part, to its effect on the bacterial community. Together, these results indicate that salinity increases microbial decomposition rates in low salinity wetlands, and suggests that these ecosystems may experience decreased soil OM accumulation, accretion, and carbon sequestration rates even with modest levels of saltwater intrusion.